2015
DOI: 10.1136/bmj.h1269
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate use and risk of lung disease in psoriasis, psoriatic arthritis, and inflammatory bowel disease: systematic literature review and meta-analysis of randomised controlled trials

Abstract: ObjeCtive To evaluate the relative risk of pulmonary disease among patients with psoriasis, psoriatic arthritis, and inflammatory bowel disease treated with methotrexate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
83
3
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(98 citation statements)
references
References 35 publications
6
83
3
6
Order By: Relevance
“…But the amount of risk increase was very small (10%) and the scope of lung diseases in this meta-analysis included all adverse respiratory events including infection. On the other hand, results from the other two meta-analysis dealing with risk of lung disease contributed by MTX and leflunomide, showed no increased risk of lung disease in MTX users [6,13]. Although those meta-analysis using randomized controlled trials compass large number of patients, the results have to be interpreted with caution because most clinical trials excluded ILD patients at enrollment.…”
Section: Lung Disease In Rheumatoid Arthritismentioning
confidence: 94%
“…But the amount of risk increase was very small (10%) and the scope of lung diseases in this meta-analysis included all adverse respiratory events including infection. On the other hand, results from the other two meta-analysis dealing with risk of lung disease contributed by MTX and leflunomide, showed no increased risk of lung disease in MTX users [6,13]. Although those meta-analysis using randomized controlled trials compass large number of patients, the results have to be interpreted with caution because most clinical trials excluded ILD patients at enrollment.…”
Section: Lung Disease In Rheumatoid Arthritismentioning
confidence: 94%
“…[36][37][38][39][40][41] Latest guidelines advise that patients stop most DMARDs if they have severe infections involving admission to hospital and/or requiring parenteral antibiotics. 36 In view of the serious interaction of trimethoprim with methotrexate, these drugs should not be co-prescribed.…”
Section: How To Adapt Routine Care For Those Taking Dmardsmentioning
confidence: 99%
“…Many patients tolerate DMARDs reasonably well 37. Intercurrent illness and drug interactions that reduce renal function can increase toxicity, particularly of methotrexate.Most DMARDs can cause pneumonitis, and there is no clear evidence for an increased risk with any specific drug[36][37][38][39] Pneumonitis is extremely rare (0.1%-1% of treated patients) and other causes for lung symptoms are much more common. Consider pneumonitis in any patient developing acute breathlessness without an obvious cause.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Methotrexate is widely used to treat psoriasis, a disease that does not affect the lungs. In patients with psoriasis receiving methotrexate, the reported lung toxicity is notably much less prevalent than in RA patients [41][42][43][44][45] . Furthermore, a study showed that the prevalence of chronic lung disease (screened with HRCT and pulmonary function tests) in RA patients receiving methotrexate does not seem to be greater than in patients receiving other treatments 46 .…”
Section: Extrapolating From the Treatment Of Other Manifestations Ofmentioning
confidence: 99%